A High-Quality Genome Assembly of the North American Song Sparrow, Melospiza melodia. Issue 4 (1st April 2020) - Louha, Swarnali; Ray, David A; Winker, Kevin; Glenn, Travis C
Abstract: The song sparrow, Melospiza melodia, is one of the most widely distributed species of songbirds found in North America. It has been used in a wide range of behavioral and ecological studies. This species' pronounced morphological and behavioral diversity across populations makes it a favorable candidate in several areas of biomedical research. We have generated a high-quality de novo genome assembly of M. melodia using Illumina short read sequences from genomic and in vitro proximity-ligation libraries. The assembled genome is 978.3 Mb, with a physical coverage of 24.9×, N50 scaffold size of 5.6 Mb and N50 contig size of 31.7 Kb. Our genome assembly is highly complete, with 87.5% full-length genes present out of a set of 4, 915 universal single-copy orthologs present in most avian genomes. We annotated our genome assembly and constructed 15, 086 gene models, a majority of which have high homology to related birds, Taeniopygia guttata and Junco hyemalis . In total, 83% of the annotated genes are assigned with putative functions. Furthermore, only ∼7% of the genome is found to be repetitive; these regions and other non-coding functional regions are also identified. The high-quality M. melodia genome assembly and annotations we report will serve as a valuable resource for facilitating studies on genome structure and evolution that can contribute to biomedical research and serve as a reference in population genomic and comparative genomic studies of closely related species.